Alterations in subgingival microbiome and advanced glycation end-products levels in periodontitis with and without type 1 diabetes mellitus: a cross-sectional study - Jialu Chen; Hong Wang; ShouShan Bu; Xiaofan Cheng; Xiaoya Hu; Min Shen; Hai Zhuang (BMC Oral Health)
Abstract Background Existing studies predominantly focused on the relationship between periodontitis and type 2 diabetes mellitus (T2DM), with limited data on the association between periodontitis and type 1 diabetes mellitus (T1DM). This study aimed to examine the impact of T1DM and periodontitis on the subgingival microbiome and levels of advanced glycation end-products (AGEs). Methods Samples were collected from four groups: T1DM, periodontitis (P), T1DM with periodontitis (DP), and periodontally and systemically healthy controls (Control). Subgingival microbiome composition and AGE levels were assessed using 16S rRNA gene sequencing and enzyme-linked immunosorbent assay (ELISA), respectively. Correlations between clinical indexes, microbiome composition, and AGEs were analyzed using Spearman correlation coefficient. Results Alpha and beta diversity analyses revealed significant differences in bacterial diversity between the DP group and other groups. Linear discriminant analysis effect size (LEfSe) analysis identified specific bacteria influencing each group: Acinetobacter, Leptotrichia, Raoultibacter, and Veillonella in the Control group; Tannerella, Porphyromonas, Filifactor, and Treponema in the P group; and Lactobacillales in T1DM individuals. Prevotella and Selenomonas were notably influential in the DP group. PICRUSt2 analysis showed pathways alterations were concentrated in cell motility, translation, cell growth and death and metabolism in the DP and P groups. Spearman correlation analysis indicated a positive correlation between AGEs and periodontitis or diabetes-related parameters and AGEs were positively correlated with Haemophilus and Arachnia. Conclusions The findings suggested that the composition and function of the subgingival microbiome in the P group with or without T1DM were significantly different. Additionally, AGEs were involved in the development of periodontitis even in absence of hyperglycemia.